Elastic electron scattering from 17Ne and 27P exotic nuclei - Ridha, A. R. (Iraqi Journal of Physics, 2019)
The ground state proton, neutron and matter densities and corresponding root mean square radii of unstable proton-rich 17Ne and 27P exotic nuclei are studied via the framework of the twofrequency shell model. The single particle harmonic oscillator wave functions are used in this model with two different oscillator size parameters core b and halo , b the former for the core (inner) orbits whereas the latter for the halo (outer) orbits. Shell model calculations for core nucleons and for outer (halo) nucleons in exotic nuclei are performed individually via the computer code OXBASH. Halo structure of 17Ne and 27P nuclei is confirmed. It is found that the structure of 17Ne and 27P nuclei have 2 5 / 2 (1d ) and 1/ 2 2s -dominant configurations, respectively. Elastic electron scattering form factors of these exotic nuclei are also studied using the plane wave Born approximation. Effects of the long tail behavior of the proton density distribution on the proton form factors of 17Ne and 27P are analyzed. It is found that the difference between the proton form factor of 17Ne and that of stable 20Ne (or of 27P and that of stable 31P) comes from the difference in the proton density distribution of the last two protons (or of the last proton) in the two nuclei. It is concluded that elastic electron scattering will be an efficient tool (in the near future) to examine proton-halo phenomena of proton-rich nuclei.